Sistem Informasi Manajemen Fakultas Teknik Universitas Teknologi Sumbawa - Shinta Esabella; Muhammad Hudzaifah Asy Syidiq; Rodianto; Muhammad Hidayatullah; Erwin Mardinata (Bulletin of Information Technology (BIT), 2022)
Currently, the governance process at the UTS Faculty of Engineering is still using a semi-digital system. Based on this, the researchers built a digital governance process management information system in the form of monitoring lecturer evaluations, judicial registration, general administration related to correspondence, and accreditation forms. The research method used is a qualitative method and a System Development Life Cycle (SDLC) with a Rapid Application Development (RAD) model as a software development method. Programming Language in making this management information system with PHP programming language which is implemented in CodeIgniter framework and MySQL database. At the end of making this information system tested using the black-box method. With this Management Information System (SIM) it can help and facilitate the management of the Faculty of Engineering in carrying out general and academic administration governance for the better. In addition, it can assist lecturers and students in completing the general administrative process related to the preparation of reports and the burden of lecturer performance as well as judicial registration for students who have completed their final assignments effectively.